The other answerers are incorrect. The formula is:
-5[x + (x + 2)] = 24 + 4(-[x + 1])
Solve:
-5(2x + 2) = 24 - 4x - 4
-10x - 10 = 20 - 4x
6x = -30
x = -30/6 = -5
The numbers are -5, -4, and -3.
Check:
-5[x + (x + 2)] = 24 + 4(-[x + 1])
-5[-5 + (-5 + 2)] = 24 + 4(-[-5 + 1])
-5(-5 - 3) = 24 + 4(5 - 1)
25 + 15 = 24 + 4(4)
40 = 24 + 16
40 = 40
2006-12-19 11:02:58
·
answer #1
·
answered by computerguy103 6
·
0⤊
0⤋
Whenever we solve any word problem involving algebra, we must first start by defining x to be some standard of comparison. In our case, we can just let x equal the first number. That means, since we have three consecutive integers:
x = the first number
x + 1 = the second number
x + 2 = the third number.
Note what we're given:
"such that -5 times the sum of the first and third ..." translates to:
(-5)[x + (x + 2)] {x is the first number, x + 2 is the third number}
"is 24 greater than 4 times the opposite of the second."
(-5)[x + (x + 2)] + 24 = 4( - [x + 1])
Note what I did above; since it is 24 greater, then you would be putting +24 to represent that. Also, the "opposite" of a number means the opposite signwise; the opposite of 5 is -5, the opposite of -17 is 17, and the opposite of (x + 1) is -(x + 1).
Thus, this is our final equation.
(-5)[x + (x + 2)] + 24 = 4( - [x + 1])
Let's simplify first. Note that x + x + 2 can be simplified, as can -(x + 1).
(-5)[2x + 2] + 24 = 4 [-x - 1]
Now, let's expand out the bracketed terms.
-10x - 10 + 24 = -4x - 4
From here, it's simple algebra. Moving all x terms to the left hand side, and everything else to the right hand side, we have
-10x + 4x = 10 - 24 - 4. Combining like terms on the left hand side, and solving the right hand side normally,
-6x = -18
Therefore,
x = 3
Remember that we LET x be our *first* integer. Our second and third integer was obtained by x + 1 and x + 2. Thus, the second integer is 3 + 1 = 4, and the third integer is 3 + 2 = 5.
So our three consecutive integers are 3, 4, and 5.
2006-12-19 18:54:49
·
answer #2
·
answered by Puggy 7
·
1⤊
1⤋
Let x be the first number so that x+1 is the second and x+2 the third.
-5(x + x+2) = 24 + 4[-(x+2)] here I hope that the "opposite" means the negative to get
-10x - 20 = 24 -4x-8
-6x = 20 + 24 -8 = 36
x = -6
x+1 = -5
x+2 = -4
2006-12-19 18:54:16
·
answer #3
·
answered by kellenraid 6
·
0⤊
1⤋
first make a key: 1st #=x, 2nd #=x+1, 3rd #=x+2
next, plug it into the equation: -5[x+(x+2)]=24+ x-1
simplified, it equals:-10x-10=23+x
simplified again:-10x=33+x
again:-11x=33
again:x=-3, so x+1=-2, and x+2=-1
2006-12-19 19:00:27
·
answer #4
·
answered by zlisa98 3
·
0⤊
1⤋